2022
DOI: 10.54393/pbmj.v5i7.611
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of High Intensity Aerobics and Pelvic Clock Exercises in Primary Dysmenorrhea

Abstract: Dysmenorrhea is very unpleasant sensation with the presence of painful cramps of uterine origin that occur during menstruation. Prevalence rate of dysmenorrhea is 50% in females’ population. Evidence tells that inactive lifestyle as well as poor diet is main reason of primary dysmenorrheal as well as women who exercise have a reduced incidence of dysmenorrhea. Objectives: To find the effectiveness of high intensity aerobics and pelvic clock exercises in primary dysmenorrhea. Methods: The study design was rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[10] Asma Qamar et al [2022] conducted a study on "Effects of High Intensity Aerobics and Pelvic Clock Exercises in Primary Dysmenorrhea" Outcome measures were calculated by visual analog scale VAS, DASS 21 and self-administered questionnaire for dysmenorrheal symptoms and concluded that that high intensity aerobics had given more efficient results rather than pelvic clock exercises. [11] Begum Kara Kaya et al [2022] conducted a study on "Comparing the Cognitive Functioning Effects of Aerobic and Pilates Exercises for Inactive Young Adults: A Randomized Controlled Trial" study concluded that, there was a significant preto post-exercise difference for participants in both groups. [12] Asmaa M. Elbandrawy et al [2021] conducted a study on "Comparison between the effects of aerobic and isometric exercises on primary dysmenorrhea" Participants were assessed using the plasma progesterone levels, visual analogue scale (VAS), and modified menstrual symptom questionnaire (MSQ).…”
Section: Discussionmentioning
confidence: 99%
“…[10] Asma Qamar et al [2022] conducted a study on "Effects of High Intensity Aerobics and Pelvic Clock Exercises in Primary Dysmenorrhea" Outcome measures were calculated by visual analog scale VAS, DASS 21 and self-administered questionnaire for dysmenorrheal symptoms and concluded that that high intensity aerobics had given more efficient results rather than pelvic clock exercises. [11] Begum Kara Kaya et al [2022] conducted a study on "Comparing the Cognitive Functioning Effects of Aerobic and Pilates Exercises for Inactive Young Adults: A Randomized Controlled Trial" study concluded that, there was a significant preto post-exercise difference for participants in both groups. [12] Asmaa M. Elbandrawy et al [2021] conducted a study on "Comparison between the effects of aerobic and isometric exercises on primary dysmenorrhea" Participants were assessed using the plasma progesterone levels, visual analogue scale (VAS), and modified menstrual symptom questionnaire (MSQ).…”
Section: Discussionmentioning
confidence: 99%